VOCATIONAL STUDENT COMPETENCE IN DIGITAL BUSINESS INDUSTRY 4.0 THROUGH MULTIMEDIA ENCOURAGEMENT AND SOCIAL BRANDING IN SASANA BUSINESS ADMINISTRATION VOCATIONAL COLLEGE, NONG CHOK DISTRICT, BANGKOK CITY WITH ABCD APPROACH - Moh. Jauharul Zulfa; Muhammad Iqbal Nazwar; Fitriah; Agus Afandi (PT. Media Akademik Publisher, 2024)
One of the successes of a country can be seen from the continuation of the relay of prosperity that continues to be carried by the next generations of the nation. As a young generation living in the era of digitalization and the industrial revolution 4.0, the factor that determines whether or not the generation is able to survive and face globalization is the ability to adapt and coexist with technology. To achieve this competency, the younger generation must be well prepared through education that is relevant to their times. Not all levels of education have the technological infrastructure academically and practically. The problem we found at SASANA College is related to the absence of academic and visionary technology facilities. So that in practical terms, the use and utilization is quite stagnant and not optimal. In this journal scientific work, we use a descriptive qualitative approach with the presentation of data in accordance with the field phenomena that occur. The focal point in this research is the students of SASANA College, Nong Chok district, Bangkok city with Asset-Based Community Engagement (ABCD) theory approach. The results showed the role of students in industry 4.0 and their competence in the utilization of multimedia in the field of digital business and our hope is that UINSA International Community Engagement students in this research will increase the progress of student competencies to think creatively and globally and provide a platform for the entire SASANA College community to integrate and live in the digital world, thus potentially increasing the social branding of the school.